Real-world experience of emicizumab prophylaxis in young children with hemophilia A: retrospective data from China - Guoqing Liu; Kun Huang; Gang Li; Yingzi Zhen; Zhengping Li; Zhenping Chen; Runhui Wu (Frontiers in Pediatrics, 2022)
BackgroundAs a new non-factor therapy for hemophilia A (HA), real-world study of emicizumab is still scarce. This study aimed to investigate the real-world use of emicizumab in Chinese boys with HA.MethodsPatients with moderate or severe HA were enrolled at Beijing Children's Hospital. They take emicizumab weekly (3 mg/kg) for a month and then went into a maintenance period with a different dosing regimen. After obtaining platelet-poor plasma at end of the loading period and during the maintenance period, coagulation ability and FVIII inhibitor were determined using human and bovine chromogenic Bethesda assay. Patients' bleeding rates were calculated through patients' records from 24 weeks before to at least 6 months after the switch (to emicizumab).ResultIn total, 13 pediatric patients with HA (severe: moderate = 11:2) were enrolled in this study. The patients' age was 3.51 (0.73–6.65) years. Eight had FVIII inhibitors at enrollment and one of them developed FVIII inhibitors again during the switch. The coagulation level of the maintenance period was 19.6 (13.5–32.8) IU/dL (N = 10). The median dose of each emicizumab injection was 2.7 (1.3–3.8) mg/kg and the monthly consumption of emicizumab was 5.2 (3.2–6.8) mg/kg/month. After switching to emicizumab, reduced annualized bleeding rate (ABR) [0.5 (0–4) vs. 4 (0–18), P < 0.01], annualized joint bleeding rate (AJBR) [0 (0–1.1) vs. 1.0 (0–12), P < 0.01], and annualized spontaneous bleeding rate (ASBR) [0 (0–1) vs. 2.0 (0–18), P < 0.01] were observed. In patients with or without FVIII inhibitor, similar ABR [0.33 (0–4) vs. 0.5 (0–3), P = 0.78], AJBR [0 (0–1.1) vs. 0 (0–0.5), P = 0.63], and ASBR [0 (0–1) vs. 0 (0–1.5), P = 0.73] were also noticed. Five inhibitor-positive patients (at enrollment) all had their inhibitor titer reduced. In addition, all target joints vanished after switching to emicizumab.ConclusionEmicizumab could reduce bleeds in pediatric patients with/without FVIII inhibitors and eliminate target joints.